Patterns of Performance on the Modified Cued Recall Test in Spanish Adults With Down Syndrome With and Without Dementia - Benejam, Bessy; Fortea, Juan; Molina-López, Rafael; Videla, Sebastià (American journal on intellectual and developmental disabilities, 2015)
The assessment of memory decline in people with intellectual disability (ID) is more difficult than in the general population, due to a lack of appropriate instruments and to preexisting cognitive impairment. The aim of this study was to describe performance of healthy adults with Down syndrome (healthy-DS; prospectively cohort) on a Spanish version of the modified Cued Recall Test (mCRT). We also recruited retrospectively a cohort of DS subjects with Dementia of the Alzheimer's Type (DS-DAT). Healthy-DS obtained higher scores on free recall and total score than DS-DAT. Age was the main factor associated with decreasing mCRT scores. The mCRT was useful in DS subjects with ID at the upper end of the spectrum or ID in the middle range of the spectrum, and discriminated well between DS subjects with and without DAT.